A ficção do eu e o outro na literatura da homossexualidade - Leandro Soares da Silva (2016)
This research deals with the reporting of biographical content, with an emphasis on literary text, and how it solves the question of subjectivity among subjects, and their identities. If, on one hand, subjectivity is applied on a prior level to the subject but, at the same time, they can cooperate with the process in order to make themselves an intelligible and able subject in the dialogue with each other, it is understood that the account in itself is a fictional and discursive strategy, in which subjects seek to acquire some agency about their subjectivities. The example used to illustrate the problem is the literary production of four male writers who, either by their biographies or literary work, have been involved with ways of identification related to homosexuality. Thus, the specific problem deals with the identification standards for homosexual males, on the one hand, and the forms of sociability, interaction and affection developed by these men, who, consequently, dialogue with or consent to the standards. The literary writing developed by the authors is evaluated in order to highlight that the subjective processes are fallible, or in other words, they are not always responsible for describing and normalizing homosexuals in the same way. Due to this, it was noted that these people continue to have their own ways of resistance and existence, which have been given the name 'homosexual ethos'. This name is the synthesis of the problem formulated above: if the subjects are always subjectified, what does it mean to narrate oneself? The narrative or report of the homosexual experience demonstrates the ineffectiveness and violence of the unique identity because, to produce a legitimate subject, it requires conformity to the standard. It is not just about heterosexual normativity; but also its homosexual equivalent. The subject who narrates themselves or their experience must continue to account for themselves not only because they are coerced by the standard which makes them legitimate, but also by telling other people who they are. This questioning of others implies the need for ethics, in which it is recognized that the subjects are not always the same, and should not necessarily match the gender expectations to be recognized and, above all, to recognize themselves. The comparison between the texts of the four authors revealed that each of them tries to answer the question 'What is a homosexual?'. The answers to this interpellation, in reality, question the actual validity of such a question, be it due to it already announcing a homosexual identity, or because it is not effective at describing individuals who have little or nothing in common. In addition, the time frame of this thesis demonstrates that the interpellation mentioned is always modulated in accordance with the masculinity standards of the time. Therefore, the subjectivity mobilized through homosexuality is not separate from types of males, and are even necessary or conditioned to them.